Evaluasi Sistem Manajemen TPQ dalam Mewujudkan Generasi Pecinta Al-Qur'an (Studi Kasus pada TPQ Hidayatul Quran Prambon Sidoarjo) - Faza Ilham; Wahyu Syafa'at; Saiful Anwar; Elok Ismakhuriya (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2025)
The evaluation of management systems in Taman Pendidikan Al-Qur'an (TPQ) is a strategic step to ensure the success of Islamic educational goals. This study aims to analyze the effectiveness of the management system in TPQ Hidayatul Quran Prambon Sidoarjo in fostering generations who love the Quran, embody noble character, and contribute to societal welfare. The research method utilized a case study approach with observation techniques, in-depth interviews, and document analysis. The findings show that the TPQ management system succeeded in training students to read the Quran according to tajweed rules, strengthening their faith, and instilling the values of noble character. However, challenges were identified in optimizing human resources and managing educational programs. This study's implications highlight recommendations for developing a more efficient and effective management model based on Islamic values to support TPQ's vision.